Radioimmunotherapy combating biofilm-associated infection in vitro - Ye, Zijian; van der Wildt, Berend; Nurmohamed, F. Ruben H. A.; van Duyvenbode, J. Fred F. Hooning; van Strijp, Jos; Vogely, H. Charles; Lam, Marnix G. E. H.; Dadachova, Ekaterina; Weinans, Harrie; van der Wal, Bart C. H.; Poot, Alex J. (Frontiers in Medicine, 2024)
Background: Addressing prosthetic joint infections poses a significant challenge within orthopedic surgery, marked by elevated morbidity and mortality rates. The presence of biofilms and infections attributed to Staphylococcus aureus (S. aureus) further complicates the scenario. Objective: To investigate the potential of radioimmunotherapy as an innovative intervention to tackle biofilm-associated infections. Method: Our methodology involved employing specific monoclonal antibodies 4497-IgG1, designed for targeting wall teichoic acids found on S. aureus and its biofilm. These antibodies were linked with radionuclides actinium-225 (225Ac) and lutetium-177 (177Lu) using DOTA as a chelator. Following this, we evaluated the susceptibility of S. aureus and its biofilm to radioimmunotherapy in vitro, assessing bacterial viability and metabolic activity via colony-forming unit enumeration and xylenol tetrazolium assays. Results: Both [225Ac]4497-IgG1 and [177Lu]4497-IgG1 exhibited a noteworthy dose-dependent reduction in S. aureus in planktonic cultures and biofilms over a 96-hour exposure period, compared to non-specific antibody control groups. Specifically, doses of 7.4 kBq and 7.4 MBq of [225Ac]4497-IgG1 and [177Lu]4497-IgG1 resulted in a four-log reduction in planktonic bacterial counts. Within biofilms, 14.8 kBq of [225Ac]4497-IgG1 and 14.8 Mbq [177Lu]4497-IgG1 led to reductions of two and four logs, respectively. Conclusions: Our findings underscore the effectiveness of [225Ac]4497-IgG1 and [177Lu]4497-IgG1 antibodies in exerting dose-dependent bactericidal effects against planktonic S. aureus and biofilms in vitro. This suggests that radioimmunotherapy might serve as a promising targeted treatment approach for combating S. aureus and its biofilm.